Recent advances in the conversion of waste cooking oil into value-added products: A review - Foo W.H.; Koay S.S.N.; Chia S.R.; Chia W.Y.; Tang D.Y.Y.; Nomanbhay S.; Chew K.W. (Elsevier Ltd, 2023)
Biodiesel; Feedstocks; Municipal solid waste; Sewage sludge; Sludge disposal; Soil pollution; Vegetable oils; Wastewater disposal; Water pollution; Biorefineries; Characterization; China and India; Environmental problems; High load; Oleochemicals; Pre-treatments; Valuable product; Value added products; Waste cooking oil; Wastewater treatment